Sensing, cognition, and engineering application [Further Thoughts] - Baker, Chris J.; Smith, Graeme E.; Balleri, Alessio; Holderied, Marc W.; Griffiths, Hugh D. (IEEE, 2014)
Definitions of cognition almost always use the term “knowing.” Sensors probe the environment producing stimuli that are interpreted to form a perception, but “knowing” is something that takes place within the brain of a human after being presented with sensed data or some form of image. Consider radar and air traffic control. A radar sensor scans the airspace and, using the principles of echolocation, is able to detect, locate, and display aircraft on a screen. An air traffic controller views the screen and continually repositions the aircraft using strict protocols that comply with safety of life requirements. In other words, it is the air traffic controller who supplies the cognitive component necessary to achieve air safety.
Keywords: Air traffic control; Cognitive science; Radar detection; Radar imaging; Sensors